DAMPAK MOTIVASI KERJA DALAM MELIHAT KINERJA KARYAWAN ROOM ATTENDANT DI SWISS-BEL HOTEL BATAM - Andri Wibowo (Puslitabmas Batam Tourism Polytecnic, 2022)
This study aims to determine the impact of work motivation to see the performance of room attendant employees at Swiss-Bel Hotel Batam. With qualitative research methods that aim to find out in depth about the opinions and perspectives of each resource person regarding the impactt of work motivation to see the performance of room attendant employees. The assessment of work motivation variables is examined from external and internal factors of work motivation itself. The results of this study indicate that work motivation affects the performance of room attendant employees at Swiss-Bel Hotel Batam. The results of this study also indicate that the external motivational factor which is very influential is an indicator of working conditions, while the working conditions in question are that the room attendants at Swiss-Bel Hotel Batam do not make employees comfortable at work so that the employee turnover rate is high. The internal factor of work motivation which is very influential is the indicator of HR selection, namely to get the opportunity for promotion without having to see how the kinship relationship with the employee of the room attendant concerned.